Attack upon a bather by a swordfish: A case report - Haddad Júnior, Vidal [UNESP]; Lima de Figueiredo, José [UNESP] (SAGE Publications, 2009)
We report a case of a bather injured by a swordfish in shallow water off the coast of southern Brazil. The victim suffered multiple injuries from the fish's bill, including a puncture wound of his left knee and the tip of the bill remaining as a foreign body. The victim made a full recovery after field management and conservative care. The potential factors leading to this most unusual attack are discussed. © 2009 Wilderness Medical Society.
Keywords: Animal attacks; Billfish injuries; Swordfish; Xiphias gladius; adult; animal; animal behavior; case report; human; injury; male; pathology; Perciformes; swimming; Adult; Animals; Behavior, Animal; Humans; Male; Swimming; Wounds and Injuries